Evaluation of Turkey's Logistics Performance Index with its Competitors in International Trade - Catuk, Cuneyt (My University, 2022)
Along with the globalized world, the disappearance of borders has ensured that every buyer in the world is seen as a potential customer. For this reason, the importance of the logistics sector is increasing every day. The Logistics Performance Index (LPI), published every two years by the World Bank, has become an important indicator to control the logistics performance of countries. In this study, eight chapters that constitute 52.9% of Turkey's exports were determined by using Turkish Statstical Institute (TUIK) data. Then, 50 countries with significant trade volume in these eight chapters in the world economy were compiled using Trendeconomics data. The data has been checked and verified with the TUIK. In order to better determine the differences, the average values of Turkey's competing countries were determined, divided into three groups on the six determinants of the LPI. Acording 50 comptetiors of Turkey based on total export and LPI, it was concluded that Turkey ranked 37th behind Vietnam, Malaysia, Greece, Indonesia. It has been determined that among the most important competitors of Turkey in international trade, Germany, Japan, Netherlands, Singapore have the best logistics performance. In order to better compare Turkey's LPI with its competitors, the countries were divided into three main groups which are High Logistic Perfomonce Group, Middle Logistic Performance Group and Low Logistic Performance Group, according to their incomes. Average LPI scores of the groups were determined and compared with Turkey. It has been determined that Turkey's most inefficient logistics aspects are Infrastructure, Customs and Tracking and Tracing. Turkey has been found to perform better in the field of International shipping and Timeliness than in MLPG.
Keywords: İşletme; Kamu Yönetimi; İktisat